Negative electrode, lithium-ion secondary battery, and lithium-ion secondary battery module
Patent Information
- Application Number
- JP2025059660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明によれば、負極活物質層中のピンホールの発生を抑制できる負極、リチウムイオン二次電池およびリチウムイオン二次電池モジュールを提供することができる。
Smart Images

Figure 2026166609000002 
Figure 2026166609000001
Abstract
Description
[Technical Field]
[0001] This invention relates to a negative electrode, a lithium-ion secondary battery, and a lithium-ion secondary battery module. [Background technology]
[0002] Carbon-based and silicon-based active materials are known as negative electrode active materials for lithium-ion secondary batteries. Silicon-based active materials are attracting attention because they can produce lithium-ion secondary batteries with higher capacity compared to those using carbon-based active materials. An example of a lithium-ion secondary battery technology using a silicon-based active material as the negative electrode active material is the one described in Patent Document 1.
[0003] Patent Document 1 describes particles containing carbon material and silicon, with a true density (He) of 1.85 g / cm³ determined by dry density measurement using helium gas. 3 More than 2.10g / cm 3 The following conditions apply: silicon content is 30% by mass or more and 80% by mass or less; oxygen content is 4.0% by mass or less; and BET specific surface area is 0.5 m². 2 / g or more 30.0m 2 The document describes composite particles with a density of less than / g. Furthermore, Patent Document 1 describes the provision of composite particles containing carbon material and silicon with reduced electrical resistivity. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] International Publication No. 2024 / 142699 [Overview of the project] [Problems that the invention aims to solve]
[0005] The present invention provides a negative electrode, a lithium ion secondary battery, and a lithium ion secondary battery module that can suppress the occurrence of pinholes in the negative electrode active material layer. Means for Solving the Problems
[0006] The present inventors conducted extensive and intensive studies to achieve the above object. As a result, the present inventors found that a negative electrode capable of suppressing the occurrence of pinholes in the negative electrode active material layer can be obtained by using a negative electrode active material containing graphite powder and Si / C powder, which has a volume change rate within a predetermined range when formed into a negative electrode slurry, and thus completed the present invention.
[0007] According to the present invention, the following negative electrode, lithium ion secondary battery, and lithium ion secondary battery module are provided.
[0008] [1] A negative electrode comprising a negative electrode active material layer containing a negative electrode active material and a binder. The negative electrode active material contains graphite powder and Si / C powder including Si-C composite particles. The negative electrode, wherein the volume change rate of the negative electrode active material measured by the following method is 3.00% or less. (Method) Distilled water is added to a solid content containing 97.0 parts by mass of the negative electrode active material and 3.0 parts by mass of the binder to prepare a negative electrode slurry with a solid content concentration of 50% by mass. Next, the negative electrode slurry is sealed in a hermetic container made of a flexible aluminum film of 30 mm × 30 mm × 5 mm, and allowed to stand at 23°C for 7 days. The volume V0 of the hermetic container immediately after sealing and the volume V1 of the hermetic container after 7 days have elapsed are measured by the Archimedes method, and the volume change rate (= 100 × (V1 - V0) / V0) is calculated. [2] The negative electrode according to [1], wherein the content of the graphite powder in the negative electrode active material layer is 50.0 parts by mass or more and 99.0 parts by mass or less when the total amount of the negative electrode active material layer is taken as 100.0 parts by mass. [3] The negative electrode according to [1] or [2], wherein the content of the Si / C powder in the negative electrode active material layer is 1.0 part by mass or more and 50.0 parts by mass or less when the total amount of the negative electrode active material layer is 100.0 parts by mass. [4] The negative electrode according to any one of [1] to [3], wherein the binder comprises one or more selected from the group consisting of polycarboxylic acid polymers and polyimide polymers. [5] The negative electrode according to [4], wherein the binder comprises a polycarboxylic acid polymer. [6] The negative electrode according to any one of [1] to [5], wherein the negative electrode active material layer further comprises a conductive additive. [7] The negative electrode according to [6], wherein the content of the conductive additive in the negative electrode active material layer is 0.01 parts by mass or more and 2.0 parts by mass or less when the total amount of the negative electrode active material layer is 100 parts by mass. [8] The negative electrode according to [6] or [7], comprising a conductive additive carbon nanotube. [9] A negative electrode according to any one of [1] to [8], further comprising a negative electrode current collector layer.
[10] The negative electrode described in [9], comprising a negative electrode current collector layer containing copper foil.
[11] Median diameter D in the volume frequency particle size distribution of the aforementioned graphite powder as determined by laser diffraction scattering. 50 A negative electrode as described in any of [1] to
[10] , wherein the diameter is 1.0 μm or more and 30.0 μm or less.
[12] Median diameter D in the volume frequency particle size distribution of the Si / C powder obtained by laser diffraction scattering method. 50 A negative electrode as described in any of [1] to
[11] , wherein the diameter is 0.5 μm or more and 20.0 μm or less.
[13] A lithium-ion secondary battery having a negative electrode as described in any of [1] to
[12] .
[14] A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in
[13] . [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a negative electrode, a lithium-ion secondary battery, and a lithium-ion secondary battery module that can suppress the generation of pinholes in the negative electrode active material layer. [Brief explanation of the drawing]
[0010] [Figure 1] This is a schematic cross-sectional view illustrating an example of a lithium-ion secondary battery according to this embodiment. [Modes for carrying out the invention]
[0011] Embodiments of the present invention will be described below with reference to the drawings. In all drawings, similar components are denoted by the same reference numeral, and explanations are omitted where appropriate. Furthermore, the drawings are schematic and do not necessarily correspond to actual dimensional proportions. In the specification, unless otherwise specified, the notation "A to B" regarding a numerical range means A or greater and B or less. For example, 1 to 5% means 1% or greater and 5% or less.
[0012] <Negative electrode> The negative electrode of this embodiment is a negative electrode comprising a negative electrode active material layer containing a negative electrode active material and a binder, wherein the negative electrode active material contains graphite powder and Si / C powder containing Si-C composite particles, and the volume change rate of the negative electrode active material by the following method is 3.00% or less. (method) A negative electrode slurry with a solid content of 50% by mass is prepared by adding distilled water to a solid content mixture containing 97.0 parts by mass of the negative electrode active material of this embodiment and 3.0 parts by mass of the binder of this embodiment. The obtained negative electrode slurry is then sealed in a sealed container made of a 30 mm × 30 mm × 5 mm flexible aluminum film and left to stand at 23°C for 7 days. The volume V0 of the sealed container immediately after sealing and the volume V1 of the sealed container after 7 days are measured by the Archimedes method, and the volume change rate (= 100 × (V1 - V0) / V0) is calculated. The negative electrode of this embodiment, by having the above configuration, can suppress the generation of pinholes in the negative electrode active material layer.
[0013] Although the mechanism by which the above effect is obtained with the negative electrode of this embodiment is not clear, the volume change rate is thought to be an indicator of the amount of trace components with high reactivity with water among the components contained in the negative electrode active material. By keeping the volume change rate within the above range, the amount of the above trace components among the components contained in the negative electrode active material can be suppressed, and as a result, the reaction between the above trace components and the water in the negative electrode slurry can be suppressed, thus suppressing the generation of pinholes in the negative electrode active material layer.
[0014] The volume change rate of the negative electrode active material in this embodiment is 5.00% or less, preferably 3.00% or less, more preferably 2.50% or less, even more preferably 1.00% or less, even more preferably 0.70% or less, even more preferably 0.40% or less, and even more preferably 0.10% or less, from the viewpoint of suppressing the occurrence of pinholes in the negative electrode active material layer. The lower limit of the above-mentioned rate of volume change is not particularly limited, but may be, for example, 0.01% or more. Furthermore, the above volume change rate may be 0.01% or more and 5.00% or less, 0.01% or more and 3.00% or less, 0.01% or more and 2.50% or less, 0.01% or more and 1.00% or less, 0.01% or more and 0.70% or less, 0.01% or more and 0.40% or less, or 0.01% or more and 0.10% or less.
[0015] The negative electrode of this embodiment comprises a negative electrode active material layer containing a negative electrode active material and a binder.
[0016] The negative electrode active material layer of this embodiment includes a negative electrode active material and a binder. The negative electrode active material contained in the negative electrode active material layer of this embodiment includes graphite powder and Si / C powder containing Si-C composite particles. The Si / C powder of this embodiment contains Si-C composite particles, and from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, preferably the carbon material in the Si-C composite particles contains a porous carbon material, and silicon is present in at least a portion of the pores of the porous carbon material.
[0017] As a method for confirming that the Si-C composite particles of this embodiment contain silicon and carbon materials, and that silicon in the Si-C composite particles is present in at least a portion of the pores of the porous carbon material, for example, a scanning electron microscope, an energy-dispersive X-ray spectroscopic detector, and image analysis software are used to select secondary electrons as the detection target, and elemental mapping of silicon and carbon is performed on a cross-section of the Si-C composite particles under the conditions of an acceleration voltage of 3kV, 20 mapping integrations, and a magnification of 3000x, and then observed.
[0018] Examples of porous carbon materials that constitute Si-C composite particles include activated carbon, aggregates of carbon fibers, aggregates of carbon nanotubes, carbon obtained by heat treatment of resins or organic materials, and hard carbon. Porous carbon materials can be produced by known manufacturing methods such as those used to produce activated carbon or by heat treatment of polymers, but they can also be purchased commercially. The only requirement is that silicon can be generated or incorporated into the pores of the porous carbon, and the materials are not limited to these methods.
[0019] Median diameter D in the volume frequency particle size distribution of Si / C powder according to the laser diffraction scattering method of this embodiment 50 The particle size is preferably 0.5 μm to 20.0 μm, more preferably 1.0 μm to 15.0 μm, even more preferably 1.5 μm to 14.0 μm, even more preferably 2.0 μm to 13.0 μm, and even more preferably 2.5 μm to 12.0 μm.
[0020] In this embodiment, the following methods can be used to measure the volume frequency particle size distribution of the Si / C powder. First, the Si / C powder is suspended in a dispersion medium and dispersed using ultrasonic waves. Next, the volume frequency particle size distribution of the Si-C composite particles is measured using a laser diffraction particle size distribution analyzer by laser diffraction scattering. The measurement is performed five times, and the arithmetic mean of the obtained values can be used.
[0021] In this embodiment, the method for producing Si / C powder is not particularly limited, but for example, a median diameter of 4.0 to 12.0 μm and a specific surface area of 800 to 1800 m² may be used. 2 Si / C powder can be obtained by a manufacturing method in which a porous carbon material of 1 / g is placed in a tubular furnace, the furnace is replaced with argon gas, and then a mixed gas of silane gas and nitrogen gas containing 1-3 mol% silane gas is flowed into the tubular furnace at a flow rate of 250-350 sccm, and the process is carried out under conditions of 450-550°C, 700-800 Torr, and 90-150 minutes. Furthermore, the manufacturing method of Si / C powder preferably further includes a step of applying a carbon coating to the Si / C powder. It is believed that the amount of Si on the surface of the Si-C composite particles can be reduced by carbon coating. Known methods can be used for the step of applying a carbon coating to the Si / C powder, such as chemical vapor deposition (CVD) or liquid phase coating, and it is preferable to use the CVD method. When carbon coating is performed by the CVD method, it is preferable to have a large supply of the gas that serves as the carbon source (e.g., methane or ethylene), specifically, it is preferable to supply 10 mL / min to 20 mL / min for 10 to 20 minutes. The reason why a larger supply of carbon-source gas is preferable is that the gas supply affects the thickness of the carbon coating, and a thicker carbon coating can suppress the presence of trace components in the Si / C powder that are highly reactive with water on the surface of the Si / C powder.
[0022] When the total of the negative electrode active material layer of the present embodiment is taken as 100.0 parts by mass, the content of the Si / C powder in the negative electrode active material layer is preferably 1.0 parts by mass or more and 50.0 parts by mass or less, more preferably 5.0 parts by mass or more and 40.0 parts by mass or less, still more preferably 8.0 parts by mass or more and 30.0 parts by mass or less, still more preferably 10.0 parts by mass or more and 28.0 parts by mass or less, and still more preferably 12.0 parts by mass or more and 25.0 parts by mass or less.
[0023] From the viewpoint of further improving the battery performance of the obtained lithium ion secondary battery, the graphite powder of the present embodiment is preferably graphite powder containing amorphous carbon on the surface. Further, it is preferable to use a combination of graphite powder containing amorphous carbon on the surface and graphite powder containing no amorphous carbon on the surface as the graphite powder.
[0024] When a combination of graphite powder containing amorphous carbon on the surface and graphite powder containing no amorphous carbon on the surface is used as the graphite powder, the mass ratio (M2 / M1) of the content M2 of the graphite powder containing no amorphous carbon on the surface to the content M1 of the graphite powder containing amorphous carbon on the surface in the negative electrode active material layer of the present embodiment is preferably 0.1 or more and 10.0 or less, more preferably 0.2 or more and 5.0 or less, still more preferably 0.3 or more and 3.0 or less, still more preferably 0.4 or more and 2.0 or less, and still more preferably 0.6 or more and 1.5 or less, from the viewpoint of further improving the cycle characteristics of the obtained lithium ion secondary battery.
[0025] The median diameter D in the volume frequency particle size distribution of the graphite powder of the present embodiment measured by a laser diffraction scattering method 50 is preferably 1.0 μm or more and 30.0 μm or less, more preferably 3.0 μm or more and 25.0 μm or less, still more preferably 5.0 μm or more and 24.0 μm or less, still more preferably 6.0 μm or more and 22.0 μm or less, and still more preferably 8.0 μm or more and 20.0 μm or less.
[0026] In this embodiment, the graphite powder content is preferably 50.0 parts by mass or more and 99.0 parts by mass or less, more preferably 60.0 parts by mass or more and 95.0 parts by mass or less, even more preferably 65.0 parts by mass or more and 90.0 parts by mass or less, even more preferably 68.0 parts by mass or more and 85.0 parts by mass or less, and even more preferably 70.0 parts by mass or more and 85.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass.
[0027] Examples of binders in the negative electrode active material layer of this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); polycarboxylic acid polymers such as poly(meth)acrylic acid; polyimide polymers such as polyimide and polyamideimide; conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination. Among these, the binder in the negative electrode active material layer of this embodiment preferably comprises one or more selected from the group consisting of fluororesin, polycarboxylic acid polymer, polyimide polymer, and synthetic rubber, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery; more preferably comprises one or more selected from the group consisting of polyvinylidene fluoride, polycarboxylic acid polymer, polyimide polymer, and styrene-butadiene rubber; and even more preferably comprises one or more selected from the group consisting of polycarboxylic acid polymer and polyimide polymer.
[0028] The binder included in the negative electrode active material layer of this embodiment preferably includes a polycarboxylic acid polymer, from the viewpoint of reducing the volume change rate of the negative electrode active material of this embodiment while further suppressing the occurrence of pinholes in the negative electrode active material layer. In this specification, a polycarboxylic acid polymer means a polymer containing an unsaturated carboxylic acid or a salt thereof as a monomer unit. Examples of unsaturated carboxylic acids or salts thereof include acrylic acid or a salt thereof, methacrylic acid or a salt thereof, maleic acid or a salt thereof, fumaric acid or a salt thereof, and among these, preferably one or more selected from the group consisting of acrylic acid or a salt thereof and methacrylic acid or a salt thereof, more preferably containing acrylic acid or a salt thereof, and even more preferably containing acrylic acid. Furthermore, alkali metal salts (e.g., Li, Na, K, etc.) are preferred as salts. The polycarboxylic acid polymer of this embodiment preferably comprises a polycarboxylic acid, more preferably at least one selected from the group consisting of polyacrylic acid and polymethacrylic acid, and even more preferably polyacrylic acid.
[0029] In the negative electrode of this embodiment, the negative electrode active material layer preferably further contains a conductive additive from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.
[0030] Examples of conductive additives in the negative electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon black such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination. Among these, the conductive additive in the negative electrode active material layer of this embodiment preferably contains carbon materials, more preferably carbon nanotubes, and even more preferably single-walled carbon nanotubes, from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery.
[0031] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the content of the conductive additive in the negative electrode active material layer of this embodiment is preferably 0.01 parts by mass or more and 2.0 parts by mass or less, more preferably 0.02 parts by mass or more and 1.5 parts by mass or less, even more preferably 0.03 parts by mass or more and 1.0 part by mass or less, even more preferably 0.05 parts by mass or more and 0.8 parts by mass or less, and even more preferably 0.08 parts by mass or more and 0.5 parts by mass or less, when the total amount of the negative electrode active material layer is 100 parts by mass.
[0032] The specific surface area of the carbon nanotubes in the negative electrode active material layer of this embodiment, as measured by the nitrogen adsorption BET method, is preferably 300 m², from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery. 2 / g or more, more comfortably 350m 2 / g or more, more preferably 400m 2 / g or more, more preferably 450m 2 / g or more, more preferably 500m 2 It is 1500 m² or more. There is no particular limit to the upper limit of the specific surface area of carbon nanotubes in the negative electrode active material layer of this embodiment, but for example, 1500 m² 2 It may be less than / g, and 1200m 2 It may be less than / g, and 1000m 2 It may be less than / g. From the viewpoint of further improving the performance balance between energy density and cycle characteristics of the resulting lithium-ion secondary battery, the specific surface area of the carbon nanotubes in the negative electrode active material layer of this embodiment is preferably 300 m². 2 / g or more 1500m 2 / g or less, more preferably 350m 2 / g or more 1200m 2 / g or less, more preferably 400m 2 / g or more 1000m 2 / g or less, more preferably 450m 2 / g or more 1000m 2 / g or less, more preferably 500m 2 / g or more 1000m 2It is less than / g. The specific surface area of carbon nanotubes can be measured by the method described in the examples.
[0033] The aspect ratio of the carbon nanotubes in this embodiment is preferably 100 or more, more preferably 250 or more, even more preferably 500 or more, even more preferably 750 or more, and even more preferably 1000 or more, from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery. There is no particular upper limit to the aspect ratio of the carbon nanotubes in this embodiment, but it may be, for example, 100,000 or less, 50,000 or less, 20,000 or less, 10,000 or less, or 7,500 or less. The aspect ratio of the carbon nanotube in this embodiment may be 100 to 100,000, 250 to 50,000, 500 to 20,000, 750 to 10,000, or 1,000 to 7,500, from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the lithium-ion secondary battery.
[0034] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the thickness of the negative electrode active material layer in this embodiment is preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, and even more preferably 50 μm to 150 μm.
[0035] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the density of the negative electrode active material layer in this embodiment is preferably 0.50 g / cm³. 3 More than 3.00g / cm 3 More preferably, 1.00 g / cm³ 3 More than 2.50g / cm 3 More preferably, 1.30 g / cm³ 3 More than 2.00g / cm 3 The following applies:
[0036] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the negative electrode of this embodiment preferably further includes a negative electrode current collector layer.
[0037] The negative electrode current collector layer of this embodiment includes a negative electrode current collector formed of, for example, aluminum, stainless steel, nickel, titanium, or an alloy thereof, and preferably a negative electrode current collector formed of copper. The shape of the negative electrode current collector may be, for example, foil, a flat plate, or a mesh, and preferably foil. Therefore, the negative electrode current collector layer of this embodiment preferably includes copper foil. The thickness of the negative electrode current collector is not particularly limited, but for example, it is 1 μm or more and 50 μm or less.
[0038] <Lithium-ion rechargeable battery> The lithium-ion secondary battery of this embodiment is equipped with the negative electrode of this embodiment. Since the lithium-ion secondary battery of this embodiment is equipped with a negative electrode containing the negative electrode active material of this embodiment, the occurrence of pinholes in the negative electrode active material layer can be suppressed.
[0039] The lithium-ion secondary battery of this embodiment will be described with reference to the figures. Figure 1 is a schematic cross-sectional view showing an example of the lithium-ion secondary battery of this embodiment. As shown in Figure 1, the lithium-ion secondary battery 10 comprises the negative electrode, electrolyte, and positive electrode of this embodiment. A separator 5 can also be provided between the positive electrode and the negative electrode. Multiple pairs of positive and negative electrodes can be provided.
[0040] The lithium-ion secondary battery 10 has a positive electrode comprising a positive electrode current collector 3 made of a metal such as aluminum foil and a positive electrode active material layer 1 containing a positive electrode active material provided thereon, and a negative electrode comprising a negative electrode current collector 4 made of a metal such as copper foil and a negative electrode active material layer 2 containing a negative electrode active material provided thereon. The positive electrode and the negative electrode are laminated via a separator 5 made of a nonwoven fabric or a polypropylene microporous film, for example, so that the positive electrode active material layer 1 and the negative electrode active material layer 2 face each other. This electrode pair is housed in a container formed of an outer casing 6, 7 made of an aluminum laminate film, for example. A positive electrode tab 9 is connected to the positive electrode current collector 3 and a negative electrode tab 8 is connected to the negative electrode current collector 4, and these tabs are led out of the container. An electrolyte is injected into the container and sealed. A structure in which a group of electrodes, each consisting of multiple laminated electrode pairs, is housed in the container is also possible.
[0041] The lithium-ion secondary battery 10 can be manufactured according to known methods. For electrodes, for example, laminates or wound bodies can be used. For the outer casing, metal casings or aluminum laminate casings can be used as appropriate. The shape of the battery may be any shape, such as coin type, button type, sheet type, cylindrical type, prismatic type, or flat type.
[0042] In the lithium-ion secondary battery of this embodiment, the positive electrode preferably comprises a positive electrode active material layer containing a positive electrode active material and a positive electrode current collector. The positive electrode active material layer of this embodiment preferably comprises a positive electrode active material and a binder, and more preferably comprises a positive electrode active material, a binder and a conductive additive.
[0043] The positive electrode active material in the positive electrode active material layer of this embodiment may be, for example, lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-cobalt-manganese-aluminum composite oxide, and other composite oxides of lithium and transition metals; transition metal sulfides such as TiS2, FeS, MoS2; and MnO, V2O5, V6O 13 Examples include transition metal oxides such as TiO2, and olivine-type lithium phosphate oxides. One of these may be used alone, or two or more may be used in combination.
[0044] Examples of conductive additives in the positive electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjenblack; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination.
[0045] Examples of binders in the positive electrode active material layer of this embodiment include fluorine-based binders such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF); and aqueous binders such as styrene-butadiene rubber. One of these may be used alone, or two or more may be used in combination.
[0046] The positive electrode current collector of this embodiment may be made of, for example, aluminum, stainless steel, nickel, titanium, or an alloy thereof. The shape of the positive electrode current collector may be, for example, foil, a flat plate, or a mesh. The thickness of the positive electrode current collector is not particularly limited, but for example, it is 1 μm or more and 50 μm or less.
[0047] Examples of electrolytes in this embodiment include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), and butylene carbonate (BC); linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC); aliphatic carboxylic acid esters; γ-lactones such as γ-butyrolactone; linear ethers; and cyclic ethers, in which lithium salts such as lithium hexafluoride phosphate (LiPF6), lithium borofluoride (LiBF4), LiFSI, and lithium perchlorate (LiClO4) are dissolved. The organic solvent may be used alone or in combination of two or more.
[0048] The separator of this embodiment is, for example, mainly made of a porous membrane, woven fabric, nonwoven fabric, etc., and as the resin component, for example, polyolefin resins such as polypropylene and polyethylene, polyester resins, acrylic resins, styrene resins, or nylon resins can be used. In addition, if necessary, a layer containing inorganic particles may be formed in the separator, and examples of inorganic particles include insulating oxides, nitrides, sulfides, carbides, etc.
[0049] As the outer casing of this embodiment, for example, a case or can made of a flexible film can be used, and from the viewpoint of reducing the weight of the battery, it is preferable to use a flexible film. The flexible film can be one in which a resin layer is provided on both the front and back surfaces of a metal base layer. The metal layer can be selected to have barrier properties such as preventing leakage of electrolyte and intrusion of moisture from the outside, and can be made of aluminum, stainless steel, etc. A heat-sealable resin layer, such as a modified polyolefin, is provided on at least one surface of the metal layer. The outer casing is formed by facing the heat-sealable resin layers of the flexible film toward each other and heat-sealing the area around the part that houses the electrode laminate. A resin layer such as a nylon film or polyester film can be provided on the surface of the outer casing opposite to the surface on which the heat-sealable resin layer is formed.
[0050] <Lithium-ion secondary battery module> The lithium-ion secondary battery module of this embodiment comprises the lithium-ion secondary battery of this embodiment. Since the lithium-ion secondary battery of this embodiment can suppress the generation of pinholes in the negative electrode active material layer, the lithium-ion secondary battery module of this embodiment can suppress the generation of pinholes in the negative electrode active material layer.
[0051] The lithium-ion secondary battery module of this embodiment preferably includes two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes a housing capable of housing two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes one or more selected from the group consisting of a protection circuit to protect the lithium-ion secondary batteries from overcurrent, a balance circuit to equalize the voltage between the electrodes of the lithium-ion secondary batteries, a controller to control the lithium-ion secondary batteries, a cooler capable of cooling the lithium-ion secondary batteries, and a heater capable of heating the lithium-ion secondary batteries.
[0052] The lithium-ion secondary battery module of this embodiment can be used in a battery system comprising multiple electrically connected lithium-ion secondary battery modules and a battery control system. Examples of battery systems include battery packs, stationary battery systems, automotive power battery systems, automotive auxiliary battery systems, and emergency power supply battery systems.
[0053] The embodiments of the present invention have been described above, but these are merely examples, and various other configurations can also be adopted.
[0054] It should be noted that the present invention is not limited to the embodiments described above, and any modifications, improvements, etc., that can achieve the objectives of the present invention are included in the present invention. [Examples]
[0055] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto.
[0056] <Measurement of Specific Surface Area of Graphite Powder, Positive Electrode Active Material, and Conductive Additive> For the graphite powder, positive electrode active material, and conductive additive, the specific surface area was measured by the BET fluid method and the one-point method in accordance with JIS Z 8830:2013 using a fully automatic specific surface area analyzer (manufactured by Mountec Co., Ltd., Macsorb HM-1208).
[0057] <Measurement of Aspect Ratio (Fiber Length / Fiber Diameter) of Single-Walled Carbon Nanotubes> Using a scanning electron microscope, single-walled carbon nanotubes were observed under the conditions of a magnification of 5000 times and a field of view of 20 μm × 20 μm, the fiber diameter and fiber length of the single-walled carbon nanotubes were respectively measured, and the aspect ratio was calculated. A total of 100 tubes were measured, and their arithmetic mean values were respectively adopted.
[0058] <Median Diameter D of Graphite Powder, Si / C Powder, and Positive Electrode Active Material 50 Measurement> From the volume frequency particle size distribution measured by the laser diffraction scattering method using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, SALD-2300), the median diameter D at which the cumulative value is 50% 50 was determined. Here, the measurement was performed after suspending the negative electrode active material or the positive electrode active material in a dispersion medium (0.1 mass% sodium hexametaphosphate aqueous solution) and subjecting the mixture to ultrasonic dispersion. For each median diameter D 50 , the arithmetic mean value of 5 measured values was adopted.
[0059] <Production of Si / C Powder 1> Porous carbon material (D 50 : 8 μm, specific surface area: 1200 m 2 / g) was placed in a tubular furnace, the inside of the tubular furnace was purged with argon gas, then a mixed gas containing 2 mol% silane gas and 98 mol% nitrogen gas was flowed into the tubular furnace at a flow rate of 300 sccm, and the treatment was carried out by holding under conditions of 500°C, 760 Torr, and 120 minutes. Subsequently, the product was cooled to room temperature, and Si / C powder A was obtained. Si / C powder A was placed in a quartz chamber, the inside of the chamber was purged with argon gas, then the internal temperature was heated to 870°C, and ethylene gas was supplied at 15 mL / min for 10 minutes. Next, the supply of ethylene gas was stopped, heating was stopped while the inside of the chamber was filled with argon gas, and the system was cooled until the internal temperature reached room temperature, obtaining carbon-coated Si / C powder 1.
[0060] <Production of Si / C Powder 2> Porous carbon material (D 50 : 5 μm, specific surface area: 1000 m 2 / g) was placed in a tubular furnace, the same treatment as that for Si / C powder A was performed, and Si / C powder B was obtained. Si / C powder B was placed in a quartz chamber, the same treatment as that for Si / C powder 1 was performed except that ethylene gas was supplied at 20 mL / min for 20 minutes, obtaining carbon-coated Si / C powder 2.
[0061] <Production of Si / C Powder 3> Porous carbon material (D 50 : 8 μm, specific surface area: 1300 m 2 / g) was placed in a tubular furnace, the same treatment as that for Si / C powder A was performed, and Si / C powder C was obtained. Si / C powder C was placed in a quartz chamber, the same treatment as that for Si / C powder 1 was performed except that ethylene gas was supplied at 10 mL / min for 10 minutes, obtaining carbon-coated Si / C powder 3.
[0062] <Production of Si / C Powder 4> Porous carbon material (D 50 : 10 μm, specific surface area: 1400 m 2 / g) was placed in a tubular furnace, the same treatment as that for Si / C powder A was performed, and Si / C powder D was obtained. Si / C powder D was placed in a quartz chamber, and the same treatment as that for Si / C powder 1 was performed except that ethylene gas was supplied at 10 mL / min for 10 minutes, to obtain carbon-coated Si / C powder 5.
[0063] <Preparation of Si / C powder 5> Porous carbon material (D 50 : 8 μm, specific surface area: 1300 m 2 / g) was placed in a tubular furnace, the inside of the tubular furnace was purged with argon gas, then a mixed gas of 5 mol% silane gas and 95 mol% nitrogen gas was flowed into the tubular furnace at a flow rate of 300 sccm, and the treatment was performed by holding the conditions at 500° C., 760 Torr for 120 minutes. Next, the product was cooled to room temperature to obtain Si / C powder E. Si / C powder E was placed in a quartz chamber, and the same treatment as that for Si / C powder 1 was performed except that ethylene gas was supplied at 10 mL / min for 10 minutes, to obtain carbon-coated Si / C powder 5.
[0064] With respect to the cross section of the Si-C composite particles contained in each of the obtained Si / C powders, a scanning electron microscope (manufactured by Hitachi High-Tech Corporation, SU3500), an energy-dispersive X-ray spectroscopy detector (manufactured by Oxford Instruments, Ultim Max 40) and image analysis software (manufactured by Oxford Instruments, Aztec) were used, secondary electrons were selected as the detection target, and elemental mapping of silicon and carbon was performed under the conditions of an acceleration voltage of 3 kV, a mapping integration count of 20 times, and a magnification of 3000 times, and it was confirmed that the Si-C composite particles contained silicon, and in the Si-C composite particles, silicon was present in at least a part of the pores of the porous carbon material.
[0065] (Example 1) <Preparation of negative electrode active material> Graphite powder and Si / C powder 1 were mixed to obtain the negative electrode active material of Example 1. The mixing ratio of the graphite powder and Si / C powder 1 was 85:15 (mass ratio).
[0066] (Examples 2 to 4 and Comparative Example 1) The negative electrode active materials were prepared in the same manner as in Example 1, except that the type of Si / C powder and the mixing ratio of graphite powder and Si / C powder were changed as shown in Table 1.
[0067] <Measurement of volume change rate> A negative electrode slurry with a solid content of 50% by mass was prepared by adding an appropriate amount of distilled water to the solid content consisting of 97.0 parts by mass of the negative electrode active material and 3.0 parts by mass of polyacrylic acid for each example and comparative example. The obtained negative electrode slurry was sealed in a sealed container made of a 30 mm × 30 mm × 5 mm flexible aluminum film and left standing at 23°C for 7 days. The volume V0 of the sealed container immediately after sealing and the volume V1 of the sealed container after 7 days were measured by the Archimedes method, and the rate of volume change (= 100 × (V1 - V0) / V0) was calculated. The results are shown in Table 1.
[0068] <Presence or absence of pinholes in the negative electrode active material layer> A solid content of 96.9 parts by mass of negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes (SWCNTs), and 3.0 parts by mass of polyacrylic acid was used for each example and comparative example. Distilled water was added in an appropriate amount to prepare a negative electrode slurry with a solid content concentration of 50% by mass. Next, the obtained negative electrode slurry was coated onto a copper foil and then dried to obtain a negative electrode active material layer on the copper foil. The obtained negative electrode active material layer was observed using an optical microscope at 100x magnification. Layers in which no pinholes were observed were evaluated as passable (A), and those in which pinholes were observed were evaluated as failing (B). The results are shown in Table 1.
[0069] [Table 1]
[0070] The raw materials for each example and comparative example are as follows.
[0071] <Negative electrode active material layer> (Graphite powder) • Graphite powder: A mixture of artificial graphite containing amorphous carbon on its surface and artificial graphite not containing amorphous carbon on its surface, in a 1:1 (mass ratio) mixture. • Median diameter D of artificial graphite containing amorphous carbon on its surface 50 :13μm, specific surface area: 1.4m 2 / g • Median diameter D of artificial graphite that does not contain amorphous carbon on its surface 50 :10μm, specific surface area: 1.8m 2 / g (Conductive additive) Single-walled carbon nanotubes (SWCNTs, aspect ratio: 1100, specific surface area: 800 m²) 2 / g) (Binder) • Polyacrylic acid (manufactured by Sumitomo Seika Co., Ltd., AquaCharge) [Explanation of Symbols]
[0072] 1 Cathode active material layer 2 Negative electrode active material layer 3 Positive electrode current collector 4 Negative electrode current collector 5 Separators 6. Exterior 7. Exterior 8 Negative Electrode Tabs 9 Positive Tab 10 Lithium-ion rechargeable batteries
Claims
1. A negative electrode comprising a negative electrode active material layer containing a negative electrode active material and a binder, The negative electrode active material comprises graphite powder and Si / C powder containing Si-C composite particles. A negative electrode in which the volume change rate of the negative electrode active material by the method described below is 3.00% or less. (method) A negative electrode slurry with a solid content of 50% by mass is prepared by adding distilled water to a solid content mixture containing 97.0 parts by mass of the negative electrode active material and 3.0 parts by mass of the binder. The negative electrode slurry is then sealed in a sealed container made of a 30 mm × 30 mm × 5 mm flexible aluminum film and left to stand at 23°C for 7 days. The volume V of the sealed container immediately after sealing is... 0 The volume V of the sealed volume after 7 days. 1 The volume change rate (= 100 × (V)) was measured by the Archimedes method. 1 -V 0 ) / V 0 Calculate the result.
2. The negative electrode according to claim 1, wherein the content of the graphite powder in the negative electrode active material layer is 50.0 parts by mass or more and 99.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass.
3. The negative electrode according to claim 1 or 2, wherein the content of the Si / C powder in the negative electrode active material layer is 1.0 part by mass or more and 50.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass.
4. The negative electrode according to any one of claims 1 to 3, wherein the binder comprises one or more selected from the group consisting of polycarboxylic acid polymers and polyimide polymers.
5. The negative electrode according to claim 4, wherein the binder comprises a polycarboxylic acid polymer.
6. The negative electrode according to any one of claims 1 to 5, wherein the negative electrode active material layer further comprises a conductive additive.
7. The negative electrode according to claim 6, wherein the content of the conductive additive in the negative electrode active material layer is 0.01 parts by mass or more and 2.0 parts by mass or less, when the total volume of the negative electrode active material layer is 100 parts by mass.
8. The negative electrode according to claim 6 or 7, wherein the conductive additive comprises carbon nanotubes.
9. A negative electrode according to any one of claims 1 to 8, further comprising a negative electrode current collector layer.
10. The negative electrode according to claim 9, wherein the negative electrode current collector layer includes copper foil.
11. Median diameter D in the volume frequency particle size distribution of the aforementioned graphite powder as determined by laser diffraction scattering. 50 The negative electrode according to any one of claims 1 to 10, wherein the diameter is 1.0 μm or more and 30.0 μm or less.
12. Median diameter D in the volume frequency particle size distribution of the Si / C powder obtained by laser diffraction scattering method. 50 The negative electrode according to any one of claims 1 to 11, wherein the diameter is 0.5 μm or more and 20.0 μm or less.
13. A lithium-ion secondary battery comprising the negative electrode described in any one of claims 1 to 12.
14. A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in claim 13.
Citation Information
Patent Citations
Composite particles, method for producing same and use of same
WO2024142699A1